The Transfer and Development of Technology in Iranian Upstream Oil Sector: Considerations on the Concepts, Requirements, Challenges and Remedies - Masoud Derakhshan; Atefeh Taklif (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2015)
We have shown that the reliance on foreign investment within the framework of oil contracts with international oil companies has not been and will not be productive in the transfer and development of technology in Iranian upstream oil industry unless the following conditions are satisfied: i) adequate growth in the propositional and prescriptive knowledge related to oil industry to create a satisfactory absorption capacity, and ii) the active role of regulatory institutions for supervising, managing and enhancing efficiency in the market for technology to secure an effective utilization of the absorption capacity. It is emphasized that a careful identification of players in the market for oil technology transfer and development, and the realization of the processes of weakening and strengthening positions of international oil companies and service oil companies in this market, respectively, is the prerequisite in the design of optimum oil technology policies in Iran. Despite the importance of contractors in the recognition of the necessity of technological development in the chain of oil operations and conveying that to technology developers, we have noted that the scarcity of financial resources for investment in the transfer and development of technology as well as the shortcomings in the optimum utilization of the absorption capacity in Iran imply that the regulatory institutions in the market for oil technology should become more efficient and assume more active role in managing this market. It is shown that these institutions can direct the process of the transfer and development of oil technology along with the national strategies in industrial development by prioritizing the technologies which are consistent with the objectives of oil sector and at the same time having spillover effects to certain key industries in the national economy.